Abdominal cocoon syndrome. A rare cause of mechanical intestinal obstruction: A case report. (February 2023) - Mehmood, Mehwish; Mirza, Ahsan Ali; Sree, Gummadi Sai; Vakkalagadda, Naga Praneeth; Mumtaz, Hassan
Abstract: Introduction and importance: Abdominal Cocoon Syndrome (ACS) also known as Idiopathic. Sclerosing Peritonitis, is a rare cause of Mechanical Intestinal Obstruction. Case presentation: We present a 59-year-old man with severe intestinal blockage symptoms for three days. Rectum had a noticeable amount of abdominal fat. To rule out the more common causes of mechanical blockage, a CT scan revealed the presence of a rare condition called Cocoon Syndrome, which necessitated exploratory laparotomy and adhesiolysis surgery. After the surgery, the patient was declared stable and was released from the hospital. Clinical discussion: The diagnosis of a tuberculous abdominal cocoon before surgery is a real challenge. Conclusion: Recognizing and understanding this entity, as well as the usual radiological findings, may help in its appropriate treatment. Highlights: This case report found a thick fibro collagenous membrane completely or partially encases the small intestinal loops, leading to Abdominal Cocoon Syndrome. Recognizing and understanding this entity, as well as the usual radiological findings, may help in its appropriate treatment In most cases, surgery is the preferred treatment method. An early biopsy of the peritoneum can often rule out the need for surgery in most cases.